(untitled) (Journal of Educational Sciences, 2022)
This work includes a case study on formation and development of professional communicative competence of sport faculty students in the process of foreign language teaching. The article defines the significance of formation of professional communicative competence of non-linguistic specialty students (sport faculty) and identifies its components. The literature review of domestic and foreign scientists’ works on the theme of professional communicative competence has been done by the authors. The study is based on teacher’s investigation and observation of students’ effective changes in language learning. The correlation of student’s thematic preference in language learning is recently-developed within this study. A special program for students was modeled in accordance with the theme of sport nutrition. During this case study the specific features of foreign language teaching process to students of sport faculty was taken into account. All language material was selected from authentic books which definitely effected to get positive results in the end of study. The special course included the usage of interactive technologies during the classes which definitely affected to the high performance of students at the end of investigation. The applicability of the article has been proved by students’ high results and makes it possible for further potential use in foreign language teaching for students of sport faculty. Key words: professional communicative competence, non-linguistic university, teaching foreign language.